Detecting Emerging Infectious Diseases: An Overview of the Laboratory Response Network for Biological Threats. (November 2019) - Villanueva, Julie; Schweitzer, Beth; Odle, Marcella; Aden, Tricia
The Laboratory Response Network (LRN) was established in 1999 to ensure an effective laboratory response to high-priority public health threats. The LRN for biological threats (LRN-B) provides a laboratory infrastructure to respond to emerging infectious diseases. Since 2012, the LRN-B has been involved in 3 emerging infectious disease outbreak responses. We evaluated the LRN-B role in these responses and identified areas for improvement. LRN-B laboratories tested 1097 specimens during the 2014 Middle East Respiratory Syndrome Coronavirus outbreak, 180 specimens during the 2014-2015 Ebola outbreak, and 92 686 specimens during the 2016-2017 Zika virus outbreak. During the 2014-2015 Ebola outbreak, the LRN-B uncovered important gaps in biosafety and biosecurity practices. During the 2016-2017 Zika outbreak, the LRN-B identified the data entry bottleneck as a hindrance to timely reporting of results. Addressing areas for improvement may help LRN-B reference laboratories improve the response to future public health emergencies.